Revolution and War: International Entanglements in the Ottoman Transition - Derya Göçer (Gaziantep Üniversitesi Sosyal Bilimler Dergisi, 2022)
Beginning of the 20th century witnessed revolutions and wars. As the region faces such episodes again, assessing the influence of global politics on domestic context remains crucial. Inspired the International Historical Sociology approach, this work contributes to the discussion of global-domestic interaction in the emergence of agency in 1908 Young Turk Revolution and in 1920 opening of new Parliament in Ankara, Ottoman Empire. The argument is that transnational learning, a new international order, global intellectual entanglements and various other transnational connections conditioned the rise of revolutionary agency. These actors were constituted by a conjuncture of international, imperial and local factors.